Proceedings of the 2nd Annual International Conference on Advanced Material Engineering (AME 2016) 2016
DOI: 10.2991/ame-16.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of CuS-Graphene Composite

Abstract: A composite of CuS-graphene was prepared via a mild experimental condition, using copper nitrate, EDTA, glucose, carbon disulfide, ethylenediamine and graphene oxide as the raw materials. The composite was characterized by X-ray power diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy and scanning electron microscope. In this process, graphene oxide was reduced to graphene with the formation of CuS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The presence of these two peaks indicated that the NiS had been incorporated into the RGO in the composite. The peaks at 1393 and 1622 cm -1 may be attributable to the O-H deformations of the C-OH and carboxy OH in the RGO [22][23][24].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…The presence of these two peaks indicated that the NiS had been incorporated into the RGO in the composite. The peaks at 1393 and 1622 cm -1 may be attributable to the O-H deformations of the C-OH and carboxy OH in the RGO [22][23][24].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%